PENGARUH MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS DAKWAH INSTITUT AGAMA ISLAM AL-ZAYTUN INDONESIA - Amanah, Nurul; Satria, Alfi; Sobirin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Not all universities in Indonesia implement the cross-subsidy tuition system (UKT silang). In private universities, the principle of cross-subsidization cannot yet be applied, as these institutions are not managed by the government. This presents a unique challenge, especially for students at the Institut Agama Islam Al-Zaytun Indonesia (IAI AL-AZIS) who come from economically disadvantaged backgrounds. This situation can serve as a motivation for students to engage in entrepreneurial activities. By fostering entrepreneurial spirit and motivation, it is hoped that students will gain alternative sources of income to support the continuity of their studies, as well as develop life skills that will be beneficial in the future. This study aims to examine the influence of motivation on the entrepreneurial interest of students in the Faculty of Da’wah at IAI AL-AZIS. The research method used is quantitative, employing simple linear regression analysis to determine the presence of influence, and coefficient of determination analysis to measure the percentage of influence between variables. Data obtained from respondents were processed using the Statistical Product and Service Solutions (SPSS) application. The results of this study indicate a positive and significant influence between entrepreneurial motivation and students’ interest in entrepreneurship at the Faculty of Dakwah, IAI AL-AZIS. This means that as the variable of entrepreneurial motivation increases, the variable of entrepreneurial interest also increases and this result did not occur by chance but can be scientifically validated. The magnitude of the influence, based on the coefficient of determination value, is 52.2%.